Cotransport of nano-hydroxyapatite and different Cd(II) forms influenced by fulvic acid and montmorillonite colloids. (30th June 2022) - Wu, Mengmeng; Bi, Erping; Li, Binghua
Highlights: Adsorption of Cd(II) reduced charge heterogeneity of the porous media. FA/MONT colloid enhanced electrostatic repulsion between nHAP particles and sand. Secondary energy minimum and physical straining led to the retention of nHAP. FA/MONT colloid affected the amount of soluble and colloidal Cd(II). FA/MONT colloid decreased retardation effect of nHAP on Cd(II) transport. Abstract: Soil colloids can affect the cotransport of nanoparticles and pollutants. In this study, the influencing mechanisms of organic fulvic acid (FA) and inorganic montmorillonite colloid (MONT) on the cotransport of nHAP and Cd(II) were investigated. Column experiments combined with Derjaguin-Landau-Verwey-Overbeek (DLVO) theory, attachment efficiency calculation and two-site kinetic retention model were applied to study the mechanisms. Results showed that the co-existence of FA or MONT made the transport of nHAP improved by 58–75% and 33–59%, respectively. Both of them could improve the stability of nHAP particles and enhance electrostatic repulsion between nHAP particles and sand. Retention of nHAP in the sand was mainly caused by secondary energy minimum and physical straining. The co-existence of FA or MONT changed the amount of adsorbed species of Cd(II) and decreased the retardation effect of nHAP on Cd(II) transport. With increasing FA concentration, soluble FA·Cd and suspended nHAP·FA·Cd complexes in the system increased. Transport of soluble Cd(II) and total Cd(II) were strengthened due to the concentration effect of FA and the improved stability of nHAP particles. With increasing MONT concentration, the amount of soluble Cd(II) decreased, but that of colloidal Cd(II) (nHAP·Cd and MONT·Cd) increased. Due to the stronger effect of colloidal Cd(II) change than that of the soluble Cd(II) change, the transport of total Cd(II) was improved by 34–57%. The findings of this study can help to understand the fate of nanoparticles and Cd(II) in natural water and soil. Graphical abstract: Image, graphical abstract